CORNHUSK POWDERS AS ADSORBENTS FOR NITRITES IN SOLUTION: A THERMODYNAMIC AND KINETIC APPROACH - Alina Elena TROFIN; Elena UNGUREANU; Iuliana MOTRESCU; Lucia Carmen TRINCĂ; Denis Constantin ȚOPA; Diana Beatrice EPERJESSY (Journal of Applied Life Sciences and Environment, 2023)
The retention of nitrite ions in solutions of different concentrations by three cornhusks-based powders was analyzed. Natural cornhusk powder (NCHP), as waste obtained from local market, the alkalized cornhusk powder (ACHP) and the biochar from the original material (CHBC) have been characterized through scanning electron microscopy (SEM) and elemental composition EDAX – TEAM analysis (Energy dispersive analysis X-ray – Texture and ele-mental analytical microscopy) and tested for the removal of nitrite ions. The influence of initial nitrite concentration and contact time was studied under slow stirring rate conditions (150 rpm). For all three adsorbents both Freundlich and Langmuir isotherm equations described the process with R2 > 0.95, denoting physical adsorption and chemisorption on the surface. The estimated retained quantities (mg·g-1) determined from isotherms were 4.4783 (NCHP), 8.3542 (ACHP) and 8.7413 (CHBC). The Ho&McKay model was better adjusted to the adsorption data with R2 > 0.985, while the Lagergren model produced regression factors between 0.61 and 0.88. Considering the biggest concentration of nitrite solution of 50 mg·L-1 and the longest contact time of 150 minutes, the equilibrium capacity qe (mg·g-1) predicted by the Ho&McKay model for the considered adsorbents were: 4.5065 (NCHP), 8.5179 (ACHP) and 8.9445 (CHBC) compared to the obtained qt (mg·g-1) of 4.4384 (NCHP), 8.0685 (ACHP) and 8.5753 (CHBC). The nitrite uptake in the experiments reached a maximum of 2.2192 mg·g-1 on NCHP, 4.0342 mg·g-1 on ACHP and 4.2877 mg·g-1 on CHBC. Considering the cost-effective treatment steps, there is the possibility of valorising an important amount of waste as adsorbent materials.